EFFECTS OF INTRA – ROW SPACING ON THE GROWTH AND YIELD OF PEARL MILLET (Pennisetum glaucum L.) IN WARAWA AND GEZAWA SAVANNAH ZONE OF NIGERIA - IBRAHIM SULEIMAN, NURA; SANI M.G; JAFAR ABDULLAHI, IDRIS; IBRAHIM, TAJUDDEEN; UMAR M.K. (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2023)
Pearl millet (Pennisetum glaucum L.R.Br.): is locally known as gero in northern Nigeria and belongs to the family poaceae, genus Pennisetum and tribe paniceae. It is usually grown as a rain-fed crop in the dry tropics; it is an erect and tall cereal crop with determinate growth habit. It has a fibrous root system with strong lateral roots. It has the ability to withstand stress and thrive in hot region, with wide range of soil, which has made it quite popular in hot region and especially across many African countries. The aim of this research work was to determine the effect of intra- row spacing on Growth and yield of pearl Millet (Pennisetum glaucum L.R.Br.). The experiment was laid out in Randomized complete block design (RCBD) consist of twelve (12) treatments, which were replicated three (3) times, with a total of Thirty six (36) plots. The treatments comprised of three (3) intra-row spacing (25cm, 50cm and 75cm) The data collected was subjected to analysis of Variance (ANOVA) using the Genstat statistical package. Student new Man Kurl (SNK) was used to separate and compare the treatment means at 5% level of significance. Plant height, number of leaves, and leaf area, were observed as growth characters while number of stands, number of tillers, panicle length, panicle diameter, panicle weight, stover weight, 1000 seed weight and grain yield were observed as yield parameters had significant effect at (P<0.05). Based on the results of this experiment intra row spacing of (75cm) would be beneficial to pearl millet farmers in the sudan savannah zone of Nigeria. Therefore, it could be concluded that maintenance of wider intra row spacing at (75cm) influences the maximum growth and yield of pearl millet as it observed from the plot with spacing of (25cm) that produced fewer tillers compared to the plots with wider intra row spacing of (75cm) which produced more tillers and healthy plants.